Sensory, microbial and chemical effects of a slurry ice system on horse mackerel (Trachurus trachurus) - Rodríguez, Óscar; Losada, Vanesa; Aubourg, Santiago P.; Barros-Velázquez, J. (Journal of the Science of Food and Agriculture, 2005)
8 páginas, 4 tablas, 5 figuras Slurry ice, a biphasic system consisting of small spherical ice crystals surrounded by seawater, was evaluated in parallel with flake ice for the storage of horse mackerel (Trachurus trachurus). Storage in slurry ice led to a significant enhancement of shelf life (5 days for flake ice to 15 days for slurry ice), better control of pH and lower counts of total aerobes and proteolytic and lipolytic bacteria, these reaching an average difference between batches of 2, 1.43 and 1.98 log units respectively after 8 days of storage. Storage in slurry ice also involved a significantly slower formation of total volatile basic nitrogen and trimethylamine after 8 days of storage. Staphylococcus xylosus and Proteus penneri were identified as the leading proteolytic and lipolytic organisms in horse mackerel muscle. Storage of horse mackerel in slurry ice enhances the shelf life of this medium-fat fish species through better maintenance of sensory and microbiological quality. Copyright © 2004 Society of Chemical Industry This work was supported by a project granted by the Secretaría Xeral de I + D from the Xunta de Galicia (Project PGIDTI02RMA18E). Peer reviewed